Intensive probations for young adult offenders. Evaluating the impact of a non-custodial sentence - Brownlee, Ian (The British journal of criminology, 1993)
This article reviews, in brief, the use of intensive probation schemes as an alternative to custodial sentencing in England and Wales and outlines the establishment of one such project in Leeds. Having briefly detailed the project's philosophy and working practices, the article reports the findings of an evaluation of the project and concludes with some suggestions as to whether the project is operating as a genuine replacement for custody